2018
DOI: 10.1111/micc.12491
|View full text |Cite
|
Sign up to set email alerts
|

Reversible impairment of coronary flow reserve in acute myocarditis

Abstract: A reversibly impaired coronary microcirculation is a frequent finding in acute myocarditis and is associated with markers of inflammation severity. Echocardiographic CFR measurement represents a feasible and safe method for its assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Reduced coronary flow reserve (CFR) was characterized by higher levels of cardiac troponin T and larger areas of LGE on CMR. 16 The correlation of HsTn with myocardial damage has been examined in several studies following myocardial infarction. These studies showed a positive correlation of the infarct size demonstrated on CMR with troponin I levels (r ¼ 0.65, P < 0.0001), 17 although there was an inferior correlation with HsTnI (r ¼ 0.49, P < 0.001) as opposed to HsTnT (r ¼ 0.84, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced coronary flow reserve (CFR) was characterized by higher levels of cardiac troponin T and larger areas of LGE on CMR. 16 The correlation of HsTn with myocardial damage has been examined in several studies following myocardial infarction. These studies showed a positive correlation of the infarct size demonstrated on CMR with troponin I levels (r ¼ 0.65, P < 0.0001), 17 although there was an inferior correlation with HsTnI (r ¼ 0.49, P < 0.001) as opposed to HsTnT (r ¼ 0.84, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative CMR methods boast similar accuracy for the diagnosis of acute myocarditis, 15 and its correlation with troponin has been studied with respect to the coronary flow of microcirculation. Reduced coronary flow reserve (CFR) was characterized by higher levels of cardiac troponin T and larger areas of LGE on CMR 16 …”
Section: Discussionmentioning
confidence: 99%
“…That said, the presence and clinical significance of myocardial microvasculature compromise in surviving MIS‐c patients should be further investigated in the long term. It is of paramount importance to evaluate the effects of superimposed cardiovascular risk factors in this particular population, such as obesity, dyslipidemia, smoking, and systemic hypertension, which are known to impact myocardial microvascular functionality as well 23 . Understanding the key dysregulated cascade triggered by COVID‐19 in the vascular system of MIS‐c patients provides information on mediators of the pathologic process, which may help tailor successful therapeutic interventions, reducing short‐ and long‐term morbidity and mortality 21 …”
Section: Discussionmentioning
confidence: 99%
“…In the context of acute myocarditis induced by SARS‐CoV‐2, different inflammatory cells invade the myocardial architecture, release cytokines, growth factors and impair coronary microcirculation. The vascular tone of coronary microvessels is physiologically regulated by myogenic, neural, metabolic, and endothelial mechanisms, according to local demands 23 . Myocardial inflammation interferes with this precisely regulated system, induces endothelial dysfunction and microcirculatory disturbances, which finally results in myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had higher levels of cardiac troponin T and larger areas of late gadolinium enhancement at cardiac magnetic resonance. Interestingly, at three-month follow-up TTDE, CFVR was normal in all patients [86]. Within the field of renal disease, TTDE has been used to assess CFVR in patients with nephrotic syndrome.…”
Section: Other Inflammatory Conditionsmentioning
confidence: 98%